Non-Traumatic Spontaneous Spinal Subdural Hematoma in a Patient with Non-Valvular Atrial Fibrillation During Treatment with Rivaroxaban - Castillo, Jessica M. (Am J Case Rep, 2015)
Patient: Male, 69 Final Diagnosis: Spontaneous spinal subdural hematoma Symptoms: Paraplegia Medication: Rivaroxaban Clinical Procedure: — Specialty: General Internal Medicine • Hospital Medicine • Cardiology • Hematology • Neurology OBJECTIVE: Diagnostic/therapeutic accidents BACKGROUND: Spontaneous spinal subdural hematoma (SSDH) is a rare but disabling condition, accounting for only 4.1% of all intraspinal hematomas. Risk factors include arteriovenous malformations, coagulopathy, therapeutic anticoagulation, underlying neoplasms, or following spinal puncture. Vitamin K antagonists, antiplatelet agents, and heparinoids have been associated with SSDHs in prior reports. To the best of our knowledge, no cases have reported this association with the factor Xa inhibitor, rivaroxaban, and SSDHs. CASE REPORT: We report the case of a 69-year-old Honduran man with a 5-year history of symptomatic palpitations due to non-valvular atrial fibrillation. He was initially refractory to pharmacologic therapy. He underwent cardioversion in February 2014. After cardioversion, he remained asymptomatic on flecainide. He was anticoagulated on rivaroxaban 20 mg daily without incident since early 2013 until presentation in August 2014. He presented with sudden onset of excruciating upper and lower back pain after minimal movement. This was immediately followed by bilateral lower extremity paresis rapidly progressing to paraplegia with bowel and bladder dysfunction over 15 minutes. Magnetic resonance imaging demonstrated an acute spinal subdural hematoma extending from T3 inferiorly to the conus medullaris. Six months after undergoing cervical and lumbar drainage procedures, he has not recovered bowel, bladder, or lower extremity neurologic function. CONCLUSIONS: Non-traumatic spontaneous spinal subdural hematoma is a rare neurological emergency that may occur during the use of rivaroxaban in patients with non-valvular atrial fibrillation. Physicians should suspect SSDH in patients on rivaroxaban with acute onset of severe back pain and neurologic symptoms to improve the odds of a favorable outcome.